Financial Resource Mobilization in Pokhara Sub-Municipal Corporation - Thapa, Ram Bahadur (Journal of Nepalese Business Studies, 2006)
Local bodies can play a vital role in nation building process through efficient mobilization of local financial resource. Financial resource mobilization includes both raising the adequate revenue and optimal allocation of funds to meet the local people’s needs. Municipality finances its expenditures with internal and external revenues. It has to increase its efficiency in allocating financial resources to maximize the marginal productivity of resources. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.81-84